Severe Hyponatremia due to Hypopituitarism Secondary to Empty Sella Syndrome - Syed Rehan Shamim, Amir Hayat , Syed Adnan Shafqat, Maria Tabasum, Saima Afridi, Rabeeya Serfraz (Journal of Rawalpindi Medical College, 2021)
This case is about a 68 years old patient presented with worsening generalized weakness, dizziness, low mood and reduced appetite with the background history of gout and vitamin D deficiency. On general examination, the patient appeared very lethargic. However, the systemic examination was unremarkable. The vitals check showed a low blood pressure of 104/72 mm Hg. The investigations showed low levels of serum Sodium, Thyroid stimulating hormone, Cortisol. The short Synacthen test was abnormal. The anterior pituitary hormones level showed low levels of Follicle stimulating hormone, Luteinizing hormone and prolactin. CT head with contrast showed enlarged fluid filled pituitary fossa with fat. An MRI Pituitary gland showed an empty sella syndrome. The patient was hydrated initially and electrolytes were monitored regularly. Treated with hydrocortisone and thyroxine to which the patient responded and improved significantly. A follow-up appointment was arranged at endocrine clinic